Redesign of A Device to Convert Fog Into Water Using Theory of Inventive Problem Solving and Kano Methods - Indro Prakoso; Ardi Jumanto; Bhre Wangsa Lenggana; Ali Alhamidi; Sugeng Waluyo (Jurnal Ilmiah Dinamika Rekayasa, 2026)
This tudy aims to design a fog-to-water conversion device using the TRIZ (Theory of Inventive Problem Solving) and Kano methods to address clean water scarcity in high-altitude environments. The research begins with a literature-based identification of technical challenges in existing fog harvesting systems. These challenges are categorized into attributes and analyzed using TRIZ contradiction analysis, which maps improving and worsening features into a contradiction matrix. The matrix yields inventive principles such as segmentation, preliminary action, taking out, and beforehand cushioning, which generate specific solutions that form the basis of the conceptual design. Subsequently, the design is refined using the Kano method. The TRIZ-based design attributes are integrated into Kano questionnaires, which were distributed to users for data collection and analysis. The results identified 9 levels of importance and evaluated 7 functional and dysfunctional features. Of the 7 features integrated with TRIZ, 5 were selected for retention and development. This study concludes that the TRIZ method effectively resolves design conflicts and supports the development of innovative and adaptable solutions, while the Kano method validates the conceptual design based on user needs and satisfaction.